MEMBANGUN KEPERCAYAAN PASIEN MELALUI KUALITAS LAYANAN, IMAGE DAN KEPUASAN PASIEN - Woro Utari; Susetyorini; Umi Elan (JUIMA : JURNAL ILMU MANAJEMEN, 2021)
This study aims to determine and analyze the effect of service quality, image and satisfaction on patient trust at PHC Surabaya Hospital. The object of this research is PHC Surabaya Hospital with the unit of analysis in this study is the patient / patient's family. Data were collected using a questionnaire distributed to the respondents and then analyzed using SPSS. The data analysis technique in this study used descriptive analysis and multiple linear regression analysis. The results showed that most of the families using the PHC Surabaya hospital were women as much as 58%, worked as private employees and had a bachelor's education. The results also show that the service quality of the PHC Surabaya hospital is in the good category, but still needs to be improved. Based on the results of data analysis, it is known that service quality has a significant effect on patient trust. Besides, the image also has a significant effect on the patient's trust. Patient satisfaction has a significant effect on patient confidence in PHC Surabaya Hospital. Patient satisfaction has the greatest influence on patient trust.